Classroom Management Strategies in the Transformation of Education in the Digital Era: Integration of Technology and Teaching Methodologies - Lasaiba, Djamila (JENDELA PENGETAHUAN, 2024)
Technology integration into education has revolutionized the learning paradigm, driving significant transformations in teaching methodologies and learning experiences. This paper explores the multifaceted impact of digital education, emphasizing its role in addressing the demands of the digital era and enhancing inclusivity in learning environments. A comprehensive review of recent literature highlights the shift towards dynamic and interactive learning facilitated by technology, transforming teachers into facilitators of engaging educational experiences. Personalization approaches utilizing artificial intelligence and data analysis have furthered accessibility and tailored learning experiences to individual student needs, fostering a more inclusive educational landscape. Additionally, online platforms have facilitated cross-cultural collaboration and interdisciplinary learning, enriching global perspectives and expanding access to education. While digital education presents numerous benefits, challenges such as the digital divide and technology misuse require careful consideration. Issues like network instability and technological ablation hinder learning effectiveness, necessitating proactive measures for mitigation. Collaboration among schools, governments, and society is crucial in addressing infrastructure limitations and ensuring equitable access to technology-enhanced education. Furthermore, the strategic integration of online learning tools and applications offers opportunities for enhanced student engagement and personalized learning experiences. Innovative pedagogical strategies, including collaborative learning, educational games, simulations, and multimedia integration, are essential in creating effective and engaging learning environments. In conclusion, navigating the complexities of digital education requires a balanced approach that leverages technology's potential while addressing associated challenges. By fostering collaboration and innovation, education stakeholders can maximize the benefits of technology in preparing students for success in a rapidly evolving digital landscape.